Fire blazed up by violence in media – a serial killing with sexual emotion from the perspective of criminal psychology (Academic Journal of Internal Affairs, 2020)
Serial killings are extremely rare, but on the contrary they are attracting great attention. It is especially true for cases with sexual background. In Hungary are these serial crimes very seldom, therefore they draw even more attention than usual. Subject of our case study is Péter Kovács from Tiszaföldvár, who was one of the gravest killing perpetrators with certifiable sexual background in the 1950s, 1960s, and who became famous under the name the “monster of Martfű”. In the socialist era was earlier even the term „serial killing” unknown, and the ideological framework was too tight to connect several crime cases with a certain perpetrator. The criminal cases committed by the „monster of Martfű” were finally solved in detail. Based on his confession and on the evidences are the circumstances of the crimes and the methods of perpetration exactly known. Violations and traumas in his childhood, his experiences with violent films and books have not been proved in the professional literature yet. Examining the course of life of Péter Kovács is traceable how a grave trauma of his childhood formed his relation to women, and how his aggression and violent behaviour was personified under the influence of certain films and books. In the 21st century, fifty-sixty years after the occurrences is it particularly interesting to proof what kind of scenes strengthened in the perpetrator the for him irresistible feeling that he must commit violent crimes against women.
Keywords: serial killing; violence in media; criminal psychology; monster of Martfű